Agricultural facilities in the book “Al-Musannaf” by Al-Kindi (d. 557 AH/1162 AD): Irrigation methods as an example (Journal of the College of Basic Education, 2024)
The importance of this study is to highlight the historical and documentary significance of the book “Al-Musannaf” by Al-Kindi. The focus is on examining some issues related to the economic life of Omani society, particularly agricultural activities and the irrigation methods used at that time. The study addresses the problem that jurisprudential works contain many issues from which valuable historical material can be extracted. This study aims to answer the following question: What were the irrigation methods used in Omani society as described in Al-Kindi's “Al-Musannaf”?To achieve the objectives of the study, the researchers will adopt a descriptive and analytical historical approach, tracking historical information inspired by the jurisprudential discourse on the most important irrigation methods used in agricultural activity. Additionally, the study will use an inductive analytical approach to read the jurisprudential issues contained in Al-Kindi's work and extract their historical dimensions. This study concludes with several findings, the most important of which are: “Al-Musannaf” by Al-Kindi is one of the most important jurisprudential works, containing many issues that reflect various aspects of economic life in general, and agricultural activity in particular, in Omani society during the 6th century AH/12th century AD.